2019
DOI: 10.1002/ente.201900625
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfide Shuttle Suppression by Electrolytes with Low‐Density for High‐Energy Lithium–Sulfur Batteries

Abstract: A low‐density electrolyte composition is introduced for lithium–sulfur (Li–S) batteries with intrinsic and effective polysulfide shuttle suppression. Hexyl methyl ether (HME) is used in combination with 1,3‐dioxolane (DOL) as a solvent for the Li–S battery electrolyte. The choice of solvent limits the dissolution of polysulfides, leading to successful suppression of the parasitic polysulfide shuttle. Hence, high coulombic efficiencies of 98% can be obtained in coin cells for over 50 cycles. The impact of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 60 publications
2
83
1
1
Order By: Relevance
“…[119] Selective non-solvating electrolyte demonstrates the solvating power strong enough to dissolve the supporting salt but too weak to solvate the polysulfide. [120] Fluorination of some ether solvent molecules in standard electrolyte is an effective strategy to obtain such a selective non-solvating electrolyte under a low E/S ratio of 6.5 mL mg S À1 . [121] Except for leanelectrolyte operability, a mixture of hydrofluoro ether and sulfolane also inhibited the gas-producing behavior of pouch cells benefiting from their low volatility.…”
Section: Liquid-electrolyte Designmentioning
confidence: 99%
“…[119] Selective non-solvating electrolyte demonstrates the solvating power strong enough to dissolve the supporting salt but too weak to solvate the polysulfide. [120] Fluorination of some ether solvent molecules in standard electrolyte is an effective strategy to obtain such a selective non-solvating electrolyte under a low E/S ratio of 6.5 mL mg S À1 . [121] Except for leanelectrolyte operability, a mixture of hydrofluoro ether and sulfolane also inhibited the gas-producing behavior of pouch cells benefiting from their low volatility.…”
Section: Liquid-electrolyte Designmentioning
confidence: 99%
“…As a result, high-concentration electrolytes i.e., room-temperature ionic liquids, (Park et al, 2013a,b;Song et al, 2013b) solvent-in-salt, (Suo et al, 2013), and solvate ionic liquids (Dokko et al, 2013;Ueno et al, 2013;Zhang et al, 2016) have all proven quite effective at discouraging polysulfide dissolution, despite their high viscosity and subsequent poor lithium transport properties. More recently, several researchers have addressed this problem through dilution of concentrated electrolytes with poorly-coordinating solvents; work reported by Weller et al demonstrated a low-density electrolyte with high lithium salt concentration to suppress polysulfide dissolution using hexyl methyl ether in combination with DOL (Weller et al, 2019). The Wang group has recently reported good Li-S cell performance achieved from developing a "localized high concentration electrolyte" using a fluoroalkyl ether additive blended with DME electrolyte (Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[29] Within the battery research community, significant efforts have been made to improve the performance of the cell components and materials used within Li-S batteries. [25,40,[48][49][50] The selected examples are briefly summarized below.…”
Section: Limitationsmentioning
confidence: 99%
“…To tackle the issue of a low volumetric energy density (in Wh L À1 ), the mass density of the electrolyte is less important than for gravimetric energy density (in Wh kg À1 ). [49] Reducing the content of electrolyte from 3 to 1.5 μL or per mg of S active material [24] will decrease the weight of the electrolyte and the free volume required for its uptake. This is of importance, as in all known Li-S cell concepts, the electrolyte may take a large fraction of the cell (>40 % of the cell weight and volume [23,52] ).…”
Section: Energy (Gravimetric Vs Volumetric)mentioning
confidence: 99%